2022
DOI: 10.21203/rs.3.rs-1382761/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antiviral efficacy of cerium oxide nanoparticles

Abstract: Nanomaterials have been proposed as good candidates for the elimination of viruses due to their multimodal mechanisms of action. Here, we tested the antiviral potential of cerium dioxide (CeO2) nanoparticles which is largely unexplored.Two types of nano-CeO2 particles with opposing surface charge, nano-CeO2(+) and nano-CeO2(-), were assessed for their capability to decrease the plaque forming units (PFU) of four enveloped and two non-enveloped viruses during 1 h exposure. Statistically significant antiviral ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In study by Neal et al (2021) authors found that silver-modified CeO 2 NPs (AgCNPs) inactivate human coronavirus OC43, and human rhinovirus 14, and has been shown to be promising potential disinfectants (Neal et al, 2021). Nefedova et al (2022) found that CeO 2 NPs with positive, and negative surface charge have significant antiviral activity against SARS-CoV-2, influenza virus A/WSN/1933, transmissible gastroenteritis virus, bacteriophage φ6, whereas they were ineffective against picornavirus EMCV, and negatively charged CeO 2 NPs were slightly active against bacteriophage MS2 (Nefedova et al, 2022). The authors have tested also Ce 3+ ions, and SiO 2 NPs, and has reached a conclusion that antiviral activity of CeO 2 NPs is not due to the release of Ce 3+ ions or non-specific effects caused by the nano-size of particles.…”
Section: Introductionmentioning
confidence: 99%
“…In study by Neal et al (2021) authors found that silver-modified CeO 2 NPs (AgCNPs) inactivate human coronavirus OC43, and human rhinovirus 14, and has been shown to be promising potential disinfectants (Neal et al, 2021). Nefedova et al (2022) found that CeO 2 NPs with positive, and negative surface charge have significant antiviral activity against SARS-CoV-2, influenza virus A/WSN/1933, transmissible gastroenteritis virus, bacteriophage φ6, whereas they were ineffective against picornavirus EMCV, and negatively charged CeO 2 NPs were slightly active against bacteriophage MS2 (Nefedova et al, 2022). The authors have tested also Ce 3+ ions, and SiO 2 NPs, and has reached a conclusion that antiviral activity of CeO 2 NPs is not due to the release of Ce 3+ ions or non-specific effects caused by the nano-size of particles.…”
Section: Introductionmentioning
confidence: 99%